2016
DOI: 10.1371/journal.pone.0161669
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profile of Six RNA-Binding Proteins in Pulmonary Sarcoidosis

Abstract: BackgroundSarcoidosis is characterised by up-regulation of cytokines and chemokine ligands/receptors and proteolytic enzymes. This pro-inflammatory profile is regulated post-transcriptionally by RNA-binding proteins (RBPs). We investigated in vivo expression of six RBPs (AUF1, HuR, NCL, TIA, TIAR, PCBP2) and two inhibitors of proteolytic enzymes (RECK, PTEN) in pulmonary sarcoidosis and compared it to the expression in four control groups of healthy individuals and patients with other respiratory diseases: chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“… 51 Recently, decreased levels of AUF-1 mRNA were found in bronchoalveolar lavage cells and PBMC of patients with sarcoidosis, another chronic inflammatory lung disease. 52 The epithelial-specific loss of AUF-1 observed in COPD subjects in our study suggests that lower AUF-1 levels may become determinants of non-resolving inflammation, by altering the RNP complexes necessary for coordinate degradation of epithelial transcripts involved in the inflammatory response.…”
Section: Discussionmentioning
confidence: 60%
“… 51 Recently, decreased levels of AUF-1 mRNA were found in bronchoalveolar lavage cells and PBMC of patients with sarcoidosis, another chronic inflammatory lung disease. 52 The epithelial-specific loss of AUF-1 observed in COPD subjects in our study suggests that lower AUF-1 levels may become determinants of non-resolving inflammation, by altering the RNP complexes necessary for coordinate degradation of epithelial transcripts involved in the inflammatory response.…”
Section: Discussionmentioning
confidence: 60%
“…Several studies have investigated the role of PTEN in the development and progression of pulmonary sarcoidosis. The protein and mRNA expression levels of PTEN in bronchoalveolar lavage (BAL) cells of sarcoid patients were reported similar to those in the BAL cells of normal patients [ 70 72 ]. However, activation of the PI3K/Akt pathway was observed [ 70 ].…”
Section: Pten In Chronic Lung Diseasesmentioning
confidence: 82%
“…For instance, Li et al [17] found that the expression of RECK was significantly reduced in the lung tissues of COPD rats induced by chronic smoking. Navratilova et al [16] found that the expression of RECK in alveolar lavage fluid cells of COPD showed a downward trend. The low expression of RECK was also verified in in vitro cellular COPD model in our study.…”
Section: Discussionmentioning
confidence: 99%